“Without division, it’s faster, but you will take a lot of sin on your soul”. A complex peasant family in the Russian Empire in the 19th century: Main development trends - Melnikov, Pavel Yurievich (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2023)
Complex families are one of the variants of a household that combines several married couples. For a number of reasons, such families enjoyed the support of the state, landlords and the peasant community for a long time. However, after the Great Reforms, complex families began to transform under the influence of socio-economic processes. The article assesses the prevalence of a complex family among the peasant population of the Russian Empire and its changes in the second half of the 19th century.